Rola świadectwa w życiu i posłudze duszpasterzy w świetle nauczania Benedykta XVI - Przygoda, Wiesław (Verbum Vitae, 2015)
The objective of the Year for Priests proclaimed by Pope Benedict XVI was to urge priests to interior renewal and more incisive witness to the Gospel in today’s world. Although the witness to Christ and his Gospel is a common responsibility of all Christians, this primarily refers to the pastors. The central problem of this study was expressed in the question: What is the function of testimony in the life and mission of pastors? Its main source is the teaching of Pope Benedict XVI on the priesthood. The article consists of three parts: (a) the biblical basis of Christian witness (martyria); (b) the spiritual life of priests as a foundation of their testimony; and (c) several ways to implement martyria in the ministry of pastors.